Aurora kinase A promotes hepatic stellate cell activation and liver fibrosis through the Wnt/β-catenin pathway - Dai, Guanqi; Lin, Junhao; Jiang, Yuchuan; Liu, Xinhui; Chen, Peng; Zhang, Yixiao; Song, Zhenghui; Zhuang, Xuefen; Cong, Jinge; Li, Yingchun; Hong, Xuanjia; Liu, Yun; et al. (Frontiers in Oncology, 2025)
AimsAurora kinase A (AURKA) has been implicated in promoting myeloid and renal fibrosis. This study aimed to investigate the impact and underlying mechanism of AURKA on liver fibrosis and to assess the therapeutic potential of MLN8237, a small-molecule AURKA inhibitor, in preventing liver fibrosis in mice.MethodsThe research used bioinformatics analysis and immunohistochemistry staining on fibrotic liver tissues from human and mouse models to assess AURKA expression. The cellular localization of AURKA was determined through double immunofluorescence staining in human fibrotic liver tissues and primary mouse hepatic stellate cells. RNA interference and AURKA antagonism were used to examine the effects of AURKA on liver fibrosis, while RNA-sequencing, qRT-PCR, and western blotting were employed to elucidate the potential molecular mechanisms of AURKA on hepatic stellate cell activation.ResultsThe results showed that AURKA was positively correlated with the progression of liver fibrosis and was predominantly expressed in activated HSCs. Silencing AURKA inhibited HSC activation and proliferation, and induced HSC apoptosis, effects that were similar to those observed with MLN8237 treatment. Additionally, silencing AURKA suppressed the glycogen synthase kinase-3β/β-catenin signaling pathway. Pharmacological inhibition of AURKA phosphorylation also resulted in reduced liver fibrosis in vivo.ConclusionIn conclusion, AURKA may promote HSC activation and liver fibrosis through the Wnt/β-catenin pathway, suggesting its potential as a therapeutic target for liver fibrosis.